2016
DOI: 10.11603/mcch.2410-681x.2016.v0.i1.6285
|View full text |Cite
|
Sign up to set email alerts
|

The ways of free radical oxidation correction in the early posttraumatic period after the combined trauma of the chest and hips

Abstract: The article adduces the results of the research performance of reactive oxygen in the blood and liver tissue of rats in early post-traumatic period after combined chest trauma and hips. It was established that the post-traumatic period after combined chest trauma and both hips characterizing by increasing of free oxygen radicals percentage in the blood leukocyte suspensions and liver tissue after 1 day with advanced dynamics within 3 days of the experiment. It was showed the effectiveness of the emoxipin and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The results of our previous studies point to the development of tissue hypoxia in early posttraumatic period in case of combined trauma of the chest and both thighs in rats. We also have shown the increasing of reactive oxygen species contents in the blood leukocyte suspension in 24 hours of posttraumatic period with progressive dynamics 10 . Analyzing the own results and published data, we have suggested that damage of the cell plasma membrane is accompanied by their apoptotic death.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The results of our previous studies point to the development of tissue hypoxia in early posttraumatic period in case of combined trauma of the chest and both thighs in rats. We also have shown the increasing of reactive oxygen species contents in the blood leukocyte suspension in 24 hours of posttraumatic period with progressive dynamics 10 . Analyzing the own results and published data, we have suggested that damage of the cell plasma membrane is accompanied by their apoptotic death.…”
Section: Introductionmentioning
confidence: 61%
“…So, in case of experimental combined trauma of the chest and thighs a "vicious circle" has developed, which is associated with energy deficiency 10 and overproduction of free radicals, on the background of hypoxia. Superoxide anion is produced the most actively by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study of oxidative processes in the case of combined trauma of the chest and both thighs show that the most intense free-radical processes occur in the lungs on the 7 th and 14 th days of observation. On the 3 rd day of the experiment, the production of mitochondrial superoxide anion radical increases equally in the tissues of the heart and lungs, while in the tissues of the liver this rate increases to a maximum within 3-14 days [18][19][20]. It has been established that acute hyperproduction of reactive oxygen species by leukocytes in 1 day of the experiment causes disorganization of bioelectrical activity of mitochondrial membranes, which is characterized by a dynamic increase in the ratio of leukocyte cells suspension with reduced transmembrane potential and the ratio of leukocytes with signs of apoptosis with a maximum in 7 days [21].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in 14 days of observation mitochondrial apoptosis mechanisms are devalued, but increased percentage of FITC Annexin V-positive cells is remained. So, in case of experimental combined trauma of the chest and thighs "vicious circle" have developed, which is associated with energy deficiency 12 and overproduction of free radicals on the background of hypoxia. Superoxide anion the most actively is produced by mitochondria.…”
Section: Indexmentioning
confidence: 99%